Epidermal necrolysis (Stevens-Johnson syndrome/ toxic epidermal necrolysis) as extensive boundary violation: A qualitative study on the illness experience and care needs of survivors in the context of the first German guideline - Ruben Heuer; Maren Paulmann; Maja Mockenhaupt; Alexander Nast (PLoS ONE, 2025)
Background In response to considerable heterogeneity in German healthcare for patients with epidermal necrolysis (EN; also Stevens-Johnson syndrome/ toxic epidermal necrolysis), a national guideline was developed. However, no patient initiatives were identified to represent patient preferences, which have yet to be systematically evaluated in Germany. Objective We conducted a qualitative study on EN survivors’ experiences to collect contextualised data on patient preferences and identify potential shortcomings and untapped potentials in routine care. Methods We contacted 14 participants who were either survivors of EN or family members of survivors. After recruitment and obtaining informed consent, we conducted individual and dyadic interviews using a semi-structured guide developed in a preceding focus group with the same patient collective. Following grounded theory principles, recruitment was contingent on emerging themes. In our analysis, we coded interview data into thematic categories of increasing abstraction, resulting in a conceptual framework accounting for universal features of the illness experience. Results From survivors’ perspectives, EN represents a profound transgression or destabilisation of personal and interpersonal boundaries, affecting several fundamental areas of human experience. Even after returning to domestic life, survivors report physical limitations that, despite their perceived invisibility to their social environment, lead to permanent changes in self-concept and personal values. Conversely, the majority of participants emphasised restoring lost boundaries in leading an authentic and meaningful life and counteracting social alienation. The study identifies five key dimensions of boundary violations caused by EN and four areas where healthcare providers can help restore boundaries to facilitate successful coping. Conclusion Healthcare providers should be mindful of life-altering implications of EN and how debilitating illness sequelae can affect survivors beyond a transient emergency. Optimal medical care should facilitate stabilising lost boundaries over the entire recovery period and requires a sensitivity to existential aspects of the disease only accessible through a sustained dialog with patients and family members.